South African crustal fracture fluids preserve paleometeoric water signatures for up to tens of millions of years - Heard, A; Warr, O; Borgonie, G; Linage, B; Kuloyo, O; Fellowes, J; Magnabosco, C; Lau, M; Erasmus, M; Cason, E; van Heerden, E; Kieft, T; et al. (Elsevier, 2018)
Fracture fluids in Earth's crust may remain isolated for millions to billions of years, and contain information on paleohydrogeology, subsurface microbial life, and conservative components that help elucidate the atmospheric evolution of the early Earth. Examples include fluids in the South African Kaapvaal craton which host chemolithoautotrophic microbial communities that survive independent of the photosphere, and billion-year-old fluids in the Canadian Shield, which preserve the Xe isotopic signature of an evolving early atmosphere. Stable isotope analyses of the aqueous phase combined with isotopic analyses of the dissolved noble gases provide unrivalled insight into the time-alteration history of aqueous fracture fluids. Here we report stable isotope and noble gas data for fracture fluids in the Witwatersrand Basin and Bushveld Igneous Province systems, South Africa. We determine closed-system radiogenic noble gas residence times of 0.77–97 million years (Myr). Open-system residence times range between 6.0 kyr and 10.8 Myr. One sample from Masimong Mine has a mean closed-system residence time of 85 Myr, making it one of oldest paleometeoric waters ever recorded. The δ2H and δ18O of water in this sample, and in previously reported samples from the same mining district that are shown to have similar ages, require an isotopically depleted source of groundwater recharge. This could reflect a recharge regime at a higher paleolatitude, elevation, or with higher rainfall, established up to tens of Myr ago, and perhaps similar to the recharge regime in the modern Lesotho Highlands. These data suggest that groundwater isotopes can provide useful paleoclimatic information for many Myr.